(Post)colonial ports
1 online resource.
Keywords: "This book examines the role of (post)colonial ports in creating and shaping the ecotonal, cultural, historical, material, environmental, socio-political and economic contexts in formerly colonized regions, spanning the Caribbean, Africa, North America, Europe and the Pacific. The essays assess the role that literature, visual culture, architecture, archives, and ethnography can play in enriching our understanding of the complex histories of ports and port cities. They present the relation between ports and colonial infrastructure such as immigration checkpoints, detention centers, mines, plantations, shipping containers, canals, sewers, and rivers, and their impact on human and more-than-human environments. The volume approaches (post)colonial ports through the "ecotone," a concept borrowed from geography and ecology to describe a transition zone where two biological communities meet and mix-such as a forest and a grassland-to bring attention to port (non)spaces as a hinge between their environments, communities, and colonial infrastructure. It foregrounds postcolonial and decolonial approaches to the ecotone to draw attention to the cultural, ecological, and geographical dynamics that inform the social fabric of contemporary ports and port cities in the wake of empire. This volume is aimed at scholars and postgraduates across disciplines such as literature, geography, fine arts, cultural studies, and history"-- Provided by publisher.